Karakteristik Semen dan Kadar Testosteron Berdasarkan Ukuran Lingkar Skrotum Kambing Kejobong Muda dan Dewasa (CHARACTERISTICS OF SEMEN AND TESTOSTERONE LEVELS BASED ON SCROTUM CIRCUMFERENCE SIZE IN YOUNG AND ADULT KEJOBONG BUCKS) - Syamyono, Ono; Samsudewa, Daud; Setiatin, Enny Tantini (Jurnal Veteriner; Vol 16 No 2 (2015), 2015)
The aims of this research were to investigate the characteristics of semen and testosterone levels based onthe different scrotum circumference size in young and adult Kejobong bucks. The samples in the study usedwere 35 Kejobong bucks, consisted of 20 young bucks (8 months-<1 year; BW 32.52 ± 5.58 kg) and 15 adultbucks (1-2 years; BW 37.83 ± 5.95 kg). The young bucks were divided into two group categories, i.e.: scrotalcircumference size of 19.1 to 22.0 cm (M1) and 22.1 to 25.0 cm (M2). The adult bucks were also divided intotwo group categories, scrotal circumference size of 21.1 to 24.0 cm (D1) and 24.1 to 27.0 cm (D2). Surveymethod was used and the samples were determined by using purposive sampling. Testosterone levelswere measured using the ELISA test. The data were analyzed descriptively and the scrotal circumferencesize comparison was analyzed with the t-test. The results showed that the characteristics of semen andtestosterone levels in young Kejobong bucks of M1 and M2 groups were not significant (P>0.05). Similarlythe characteristics of semen and testosterone levels in adult Kejobong bucks of D1 andD2 groups were alsonot significant (P>0.05). These can be concluded that different scrotal circumference size of young andadult Kejobong bucks had similarity characteristics of semen and testosterone levels.
Keywords: characteristics of semen, scrotum circumference, testosterone and kejobong bucks